Quality Evaluation of Milk at Different Levels of Milk Chain System in Makwanpur District, Nepal - Bhattarai, Bedananda; Singha, Siyaram Prasad (Journal of Food Science and Technology Nepal, 2013)
This study assessed the quality of raw milk produced by District Milk Producers Co-operative Union (DMPCU) Makawanpur, Nepal. Five different stages (i.e. farmers, co-operative, chilling center, raw milk storage tank and pasteurization) were taken. The study revealed that adulteration was not common problem, however water addition was found to be 2.6% at farmer.s level with increase up to the 18.7% at pasteurization. Decrease in the level of conductivity from 4.32 to 3.25 mS/cm, ash from 0.76 to 0.64 %, fat from 5.38 to 2.96 %, SNF from 9.06 to 7.93%, Lactose 4.44 to 3.81% and protein from 3.1 to 2.5% was noticed from farmer.s to pasteurization level. Increase in Coliform from 4.9 log10 CFU/ml to 5.5 log10 CFU/ml from farmer.s level at raw milk to storage tank was noticed with simultaneous decreased in MBRT from 237 to 99min. Pasteurization reduced Coliform up to zero with increased in MBRT up to 309min. J. Food Sci. Technol. Nepal, Vol. 6 (80-83), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8265